Responsibility in globalisation.: Beiträge zur ethischen Bildung durch Demokratie und Menschenrechte (Pedagogical Horizons, 2020)
This article deals the role of democracy and human rights in ethical education in order to prepare students for the challenges of a globalized world.
Keywords: responsibility